PEMBUATAN HULL PERAHU IKAN CADIK FIBER GLASS SKALA KECIL BAGI MITRA KELOMPOK NELAYAN - Marasabessy, Amir; Nur, Iswadi; Hatuwe, Mohammad Rusdy (Bina Teknika, 2016)
Event Service to the community for the partner group of fishermen village of Caringin District of Labuan Pandeglang in Banten Province aims to provide training and manufacturing miniature hull fishing boat outrigger fiber glass so that partners fishermen groups can manufacture fishing boats outrigger made of fiber glass are actually independently as an attempt to divert outrigger fishing boats from wood to glass fiber materials for the development of the fishing fleet in order to maintain/increase the fish catch in order to improve the standard of living to a better direction. The method used in the manufacture of miniature outrigger fishing boat fiber glass in the form of a lecture following the discussion/question and answer and applicative training with the involvement of partner group of fishermen. Plan activities that will be done in the implementation of manufacturing miniature hull fishing boat outrigger fiber glass that provides counseling by introducing wood and fiber glass as well as equipment to be used for the manufacture of hull miniature fishing boats outrigger fiber glass, the composition of the fiber glass to see the standardization of the mixture and training manufacture of molded semi parmanen which continued with casting hull miniature outrigger fishing boats.